Self-assessment of Mental Health Among Students of Iran University of Medical Sciences - Mahnaz Solhi; Razieh Pirouzeh; zahra Rahimi Khalifeh Kend (Iranian Association of Health Education and Health Promotion, 2019)
Background and Objective: The students studying at the universities of medical sciences deal with numerous stressors during their educational experiences in the healthcare settings, which lead to poor mental health status and low performance. Regarding the role of students in the provision, maintenance and promotion of community health, this study was aimed to determine the self-assessment of mental health among students of Iran University of Medical Sciences. Methods: In this descriptive-analytical study, 300 students of the 8600 Iranian medical sciences students were randomly selected. The data collection was performed using a demographic form and a researcher-made questionnaire on self-assessment of mental health, validity and reliability of which were obtained. Data was analyzed by SPSS 16 using descriptive index and analytical tests at a significant level of 0.05. Results: The mean and standard deviation of self-assessment of students' mental health was 89.08±13.12. Also 14.7% of the students reported their mental health as poor, 70.3% as moderate and 15% as good. The mean age of the students was 25±6.21 years. The mean score of dimensions of ability to overcome anger and anger, the ability to balance the rest and activity and the ability to overcome anxiety were 3.1±0.08, 3.13±0.97 and 3.16±1.1 respectively. Also, there was a significant relationship between gender and hookah consumption with mental health (P<0.01 and P<0.009). Conclusion: Due to the low level of mental health in the dimensions of overcoming anger and anxiety and the student's role in securing and improving community health. The design of educational and promotional interventions to increase the anxiety management and anger management skills in the students is necessary to improve mental health of students.